ANALISIS DAMPAK SOSIAL EKONOMI PENGGUNA JALAN AKIBAT KEMACETAN LALU LINTAS DI BANDA ACEH - Meidianisa Aulia H (Jurnal Ekonomi dan Kebijakan Publik Indonesia, 2016)
This study aimed to determine the socio-economic impacts of the traffic jams in the city of Banda Aceh. Data used in the form of primary data obtained directly from the respondents in the field using a questionnaire, distributed to 100 respondents. The sampling technique used in this research is by using Purposive Random Sampling. Data were analyzed descriptively. These results indicate that the impact of the congestion a great effect on economic social road users, including visible side benefit is lost from the costs incurred, as well as congestion occurs makes the use of fuel oil increased as the engine starts much longer, and when viewed from the impact more socially visible from the pressure/stress and air pollution perceived road users due to congestion.